Five nights at Freddy's. Fazbear frights, graphic novel collection Vol. 1 - Cawthon, Scott, 1971-; Cooper, Elley; West, Carly Anne (Five nights at Freddy's (Scholastic Inc.), 2022)
"What do you wish for most? It's a question that Oswald, Sarah, and Oscar think they know the answer to. Oswald wishes his summer wasn't so boring, Sarah wishes to be beautiful, and Oscar wishes to get his hands on the mechanical toy that's out of stock all over town. But in the twisted world of Five Nights at Freddy's, their hearts' deepest desires have an unexpected cost. In this volume, three stories from the New York Times bestselling series Five Nights at Freddy's: Fazbear Frights come to life in delightfully horrifying comics. Readers beware: This collection of terrifying tales is enough to unsettle even the most hardened Five Nights at Freddy's fans."--back cover.